Deformation of cellular components of bone forming cells when exposed to a magnetic field - M. Iwasaka (AIP Advances, 2019)
It has been suggested that alignment control of biological macromolecules and structures is possible when the diamagnetic energy is sufficient to overcome the thermal energy. Strong magnetic fields of several Tesla (T) have previously been shown to enable the observation of the magnetic orientations of protein fibers and suspended or adherent cells. In the present study, the fine structure of a bone-forming osteoblast cell line was observed in real-time under strong static magnetic fields of up to 5 T. The magnetic field was applied normal to the adhering surface, and induced slight deformation of cellular shape under bright field illumination. A newly developed dark field observation method presented more precise analysis of the inner structures of the cells in strong magnetic fields. Specifically, structures with a round appearance were clearly visualized around the cell nucleus using the electromagnetic illumination. In addition to the magnetically induced swelling of the round structures—which showed differences in diameter of several micrometers—color changes for these intracellular components were also detected using this technique. A high-resolution analysis of fine cellular structure based on the magnetic orientation of intracellular components including microtubules is proposed.